Navigating overgrazing and cultural values through narratives and participatory mapping: a socio-cultural analysis of sheep grazing in the Faroe Islands - Verbrugge Laura NH; Bjarnason Gunnar; Fagerholm Nora; Magnussen Eyðfinn; Mortensen Lis; Olsen Erla; Plieninger Tobias; Raymond Christopher M; Olafsson Anton Stahl (TAYLOR & FRANCIS LTD, 2025)
Long-term livestock grazing has shaped landscapes, biodiversity, societies, cultures, and economies in the North Atlantic over time. However, overgrazing has become a major environmental sustainability challenge for this region, covering the Faroe Islands, Greenland, Iceland, Norway, and Scotland. The objective of this study was to elicit narratives and spatial patterns of local people's management preferences for sheep grazing in the Faroe Islands through a socio-cultural lens. We collected data via a Public Participation Geographic Information Systems (PPGIS) survey with an open question about hopes and concerns for sheep management in the Faroe Islands and a mapping exercise for expressing spatial preferences for sheep management. Four distinct narratives emerged from a qualitative analysis of responses to the open question (n = 184): (1) Sustainable sheep management, (2) Nature without sheep, (3) Sheep as part of Faroese culture, and (4) Sheep as nuisance. Visual inspection of narrative-specific maps with locations where either no or fewer sheep were preferred indicated that sheep management is not simply a 'sheep vs. no sheep' issue but embedded in a more nuanced consideration of the place of sheep in the landscape and society. For example, for some residents sheep-farming is not a commercial enterprise but a social activity and local source of food. Our combined methodological approach using qualitative and spatial data can help researchers in other fields identify the interplay between place-specific areas of grazing management concern and socio-cultural values, enabling more targeted land-use management policies or plans.